Fiduciary Shares as Collateral in Granting Credit - Gunardi Lie; Moody Rizqy Syailendra Putra; Belicia Widhyana Yulia Putri (CV. Rayyan Dwi Bharata, 2023)
In a debt agreement, of course the existence of collateral is very important so that the creditor can feel safe about the loan given to the debtor. Shares are one of the valuable and valuable intangible moving objects. Arrangements relating to shares are regulated in Law Number 40 of 2007 concerning Limited Liability Companies. Although it is not yet known the exact and clear definition of shares in Law Number 40 of 2007 concerning Limited Liability Companies, the regulation provides several provisions which are presumably related to shares. One of the interesting guarantees discussed in relation to shares is fiduciary. Fiduciary provides several arrangements related to fiduciary based on Law Number 42 of 1999 concerning Fiduciary Guarantees.